An Embedding Theorem for Medial n-ary Groupoid with Cancellation - Davidov, Sergey (Armenian Journal of Mathematics, 2015)
In 1949 M. Sholander proved that every medial cancellation groupoid can be embedded into a medial quasigroup. In this paper we prove that it is also true for n-ary cancellation groupoids, namely, every medial cancellation n-ary groupoid can be embedded into a medial n-ary quasigroup.